The role of the six sigma method in controlling and improving product quality - Suwanda, Suwanda (Sean Institute, 2024)
The Six Sigma method has been proven effective in industry for reducing process variability, increasing customer satisfaction, and optimizing operational efficiency. This research aims to analyze the role of the Six Sigma method as a systematic approach in controlling and improving product quality. This research uses qualitative methods with descriptive methods. The results of this research reveal that the application of the Six Sigma Method in controlling and improving product quality has a significant positive impact. Controlling process variability, focusing on customer satisfaction, and using statistical methods in data analysis have succeeded in increasing product consistency, building customer loyalty, and providing a strong basis for fact-based decision making. Implementation of the DMAIC concept provides a structured framework for continuous improvement, while cross-functional employee involvement creates a work environment that supports collaboration and innovation.